Upaya Pengentasan Pengangguran Anak Usia Produktif Melalui Program Rumah Gemilang Indonesia (RGI) Kelas Rekayasa Perangkat Lunak di LAZ Al-Azhar Surabaya - Maulana Asegaf; Ach Faris Zubairi (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2022)
This study discusses the efforts of LAZ Al-Azhar Surabaya in alleviating unemployment of productive age children through Software Engineering Classes Class (RPL). This study using a descriptive qualitative method that explains the effectiveness of the Software Engineering class program (RPL) at LAZ al-Azhar Surabaya. Data collected through interviews with the Head of LAZ Al-Azhar Surabaya, the head of the Software Engineering Class Program (RPL), and the beneficiaries of this program. Also collected form website, and brochures of LAZ Al-Azhar Surabaya. The the Software Engineering Class Program (RPL) has the goal of helping reduce unemployment and neglect of productive age from among the poor through computer training with the aim that after graduation they can get decent jobs. The number of beneficiaries of this program is spread throughout Indonesia. In East Java there are 26 beneficiaries from 2019-2021. Of the 26 beneficiaries, they have found jobs according to their fields. Even though some alumni have not found jobs, this program can still be said to be effective because previously the beneficiaries dropped out of school, and then with this program, the students could receive computer training for free. In the future LAZ Al-Azhar Surabaya has to provide more intense assistance to the alumni beneficiaries so that the development of alumni can be monitored and find out what obstacles are experienced by alumni and have to increase the number of beneficiaries every year so that this program can be more widely felt by the community. Keywords: Unemployment Alleviation, Software Engineering Class Program (RPL) and LAZ Al-Azhar Surabaya